Young children's personal, social and emotional development - Dowling, Marion (Los Angeles : SAGE, 2014)
This fourth edition has been full updated to include: expanded coverage of key topics including independent thinking, living and learning with others, and dispositions for learning; a new chapter on "Vulnerable children and fragile families". with sections on identifying risk, talking to families, and safeguarding and protection; guidance for working with parents in every chapter; updated links to the EYFS and a focus on two year olds. This is essential reading for all Early Years students and practitioners, and anyone working with or caring for young children.
1. The seeds of confidence and competence -- 2. Confidence and competence for learning -- 3. Living with others -- 4. Learning with others -- 5. Becoming independent -- 6. Independent thinkers -- 7. Emotional well-being -- 8. Influences on young children's well-being -- 9. Dispositions for learning -- 10. Nurturing dispositions to learn -- 11. Young children's behaviour -- 12. Achieving self-regulated behaviour -- 13. Young children's spirituality -- 14. Living in the wider world -- 15. Working with families -- 16. Vulnerable children and fragile families.
Includes bibliographical references and index.
Keywords: Child development